ACTIVE LEARNING METHODS IN THE ORGANIZATION OF THE EDUCATIONAL PROCESS - Mirxanova Matlyuba Sadikovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article is about the organization of the educational process. The organization of the educational process using active learning methods is based on a number of principles, including the principles of individualization, flexibility and cooperation.